EMOTIONAL INTELLIGENCE AS PREDICTORS OF SUICIDE IDEATION AMONG NIGERIAN YOUTHS IN FEDERAL UNIVERSITIES IN THE SOUTH-SOUTH - Okafor-Okwuchukwu, Ify-Emeka Ihuoma, Prof J.N. Onukwufor (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The study investigated emotional intelligence domains (self-awareness and self-management) as predictors of suicide ideation among Nigerian youths in Federal Universities in the South – South. A sample of 380 youths identified as suicide ideators were drawn from a population of 7851 using simple random sampling and proportionate sampling technique. The study adopted the correlational research design. Two research questions and two corresponding hypotheses guided the study. Emotional Intelligence Questionnaire (EIQ) and Suicide Ideation Scale (SIS) were used as instruments for data collection. The construct validity of the instruments was determined through factor analysis SPSS software. Copies of the multivariate instrument were administered to 30 youths for pilot test. Each instrument was subjected to factor analysis, the following coefficients were obtained; self-awareness 0.70 and self-management 0.72 while reliability index of 0.69, 0.69 and 0.79 were realized for; self-awareness, self-management and suicide ideation respectively using Cronbach Alpha Method. Simple linear regression was used to analyze the data generated. Specifically, the associated Anova was used to test the tenability of the null hypotheses at 0.05 alpha level. Findings were that self-awareness does significantly predict youths’ suicide ideation while self-management does not significantly predict Nigerian youths’ suicide ideation in South-south.